High Speed Inter-Satellite Communication System by Incorporating Hybrid Polarization-Wavelength Division Multiplexing Scheme - Chaudhary, Sushank; Chaudhary, Neha; Sharma, Saurabh; Choudhary, BC (Walter de Gruyter GmbH, 2017)
Inter-Satellite communication is one of remarkable technologies that can be used to communicate between satellites.This work is focused to carry out the investigations of polarization scheme by incorporating dense wavelength division multiplexing (DWDM) scheme in inter-satellite communication system.A 20×6 Gbps data are transported over inter-satellite optical link having span of 5,000 km to realize the total data transmission of 120 Gbps. Moreover, results are also reported with the effect of RZ and NRZ modulation schemes.The performance of proposed inter-satellite communication link is measured in terms of signal-to-noise ratio, received power and eye diagrams.